Retrospective Analysis of USG Findings in Dengue Fever as a Screening Modality - Vivek Gupta; Pranav Kumar Dave; R Mishra; M Jain; M Bapat; M Tilgam; A Patidar; J Verma; C Dave (Asian Journal of Medical Radiological Research, 2019)
Background: Dengue fever is a common public health issue in India, This study was conducted to asses value of ultrasound findings insero positive dengue cases. Subjects and Methods: Retrospective study of 81 patients of various age groups of both male and female, serologically positive for dengue fever was conducted between April-2018 to Dec-2018. These patients were referred for ultrasound of abdomen .Abdominal sonography was performed with convex probe and high frequency variable linear probes after 4-6 hours fasting .Various ultrasound finding were analyzed. Results: Out of 81 Patients Edematous gall bladder wall thickening/ edema seen in 71 (87.6%), most common findings, followed by ascites in 41 (50.6%) and Splenomegaly 17(20.9%), Hepatomegaly 15(18.5%) and pleural effusion 26 (32%).Ultrasound abdomen findings were normal in 10 (12.3%).In these Patients the platelet count  was more than 150,000..Patients with platelets count up to 80000 showed  GB wall thickening / wall edema,ascites, pleural effusion ,hepatomegaly and splenomegaly. Pericardial effusion was not seen in our study. Conclusion: Ultrasound abdomen findings of GB wall thickenings,GB wall edema, Pleural effusion, Ascites, Splenomegaly & Hepatomegaly strongly indicates diagnosis of dengue fever.These USG findings suggestive of severity of DF, which requirs proper managmeent.Subsequate USG examination helps to monitor the response to the treatment.